Trends and Developments in Physical Education for Disabilities: A Bibliometric Analysis - Apriady, Hilmy; Fitri, Mustika; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
Research in the field of Physical Education for Disabilities has experienced dynamic development. This study examines trends and advancements in physical education for disabilities through a bibliometric analysis approach. Analyzing a total of 907 articles from the period 2013 to 2023, the study aims to understand the evolution, focus, and contributions of research in this domain. Through bibliometric analysis of data obtained from the Scopus database, we investigated scientific publications related to physical education for disabilities. The use of VOSviewer software facilitated the visualization of collaboration networks among researchers, institutions, and research topics, providing deeper insights into the structure and dynamics of this research domain. This bibliometric method offers insights into research trends over time, identifies key topics of interest, and highlights contributions from various leading institutions and researchers in the field. The study underscores the importance of ongoing research and collaboration in developing physical education for disabilities. Additionally, the study includes a systematic literature review to map potential future research areas based on current trends, offering comprehensive guidance for upcoming research in this field